Medical Tourism and Hospitality in Hospital (The Gaze: Journal of Tourism and Hospitality, 2019)
Medical tourism is a growing phenomenon with policy implications for health systems, particularly of destination countries. Both private sectors and the governments of such destinations are found playing important role for medical tourism promotion and development. This study tries to highlight a conceptual analysis of medical tourism, the targeting of medical tourism flows and major destinations, and the proposed medical tourism development strategies based on the experience of several countries regarding medical facilities. Medical tourism, where patients travel overseas for operations, has grown rapidly in the past decade, especially cosmetic surgery. The review of current literature reveals that no integrated theoretical framework for the holistic study of the medical tourism industry exists. This study examined whether the scholars who studied medical tourism and hospitality in hospitals found interrelationship between those two different sectors. Those who studied medical tourism or healthcare tourism didn’t touch on hospitality provided to hospital patients. Likewise, those who studied hospitality in hospitals also ignored the dimension of tourism. In this regard, this study shows the interrelationship between these two entities. i.e medical tourism and hospitality in hospitals which are very important for understanding the concept of medical tourism in better way. Additionally, this study also enters the sphere of cross cultural behavior and intercultural communication between the hosts and the guests.